2005
DOI: 10.1007/s00221-005-0080-4
|View full text |Cite
|
Sign up to set email alerts
|

Hand preshaping in Parkinson’s disease: effects of visual feedback and medication state

Abstract: Previous studies in our laboratory examining pointing and reach-to-grasp movements of Parkinson's disease patients (PDPs) have found that PDPs exhibit specific deficits in movement coordination and in the sensorimotor transformations required to accurately guide movements. We have identified a particular difficulty in matching unseen limb position, sensed by proprioception, with a visible target. In the present work, we further explored aspects of complex sensorimotor transformation and motor coordination usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
69
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 99 publications
10
69
1
1
Order By: Relevance
“…akinesia and bradykinesia [9][10][11], rigidity [12,13], and resting tremor [9,10,14], but has shown modest effects on restoring coordinated movements when demands on precision are high, such as for prehensile actions or reaching/ pointing toward a target. For example, dopamine replacement therapy failed to improve some aspects of reach-to-grasp actions [15,16] and reaching movements [17,18], and even led to increased spatial errors [11]. Disruptions in movement amplitude and velocity, which we have termed intensive aspects of movement, may be amendable to dopamine replenishment therapy [15] perhaps due to thalamo-cortical disinhibition resulting in an increase of BGthalamocortical signals to the primary and supplementary motor areas [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…akinesia and bradykinesia [9][10][11], rigidity [12,13], and resting tremor [9,10,14], but has shown modest effects on restoring coordinated movements when demands on precision are high, such as for prehensile actions or reaching/ pointing toward a target. For example, dopamine replacement therapy failed to improve some aspects of reach-to-grasp actions [15,16] and reaching movements [17,18], and even led to increased spatial errors [11]. Disruptions in movement amplitude and velocity, which we have termed intensive aspects of movement, may be amendable to dopamine replenishment therapy [15] perhaps due to thalamo-cortical disinhibition resulting in an increase of BGthalamocortical signals to the primary and supplementary motor areas [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, dopamine replacement therapy failed to improve some aspects of reach-to-grasp actions [15,16] and reaching movements [17,18], and even led to increased spatial errors [11]. Disruptions in movement amplitude and velocity, which we have termed intensive aspects of movement, may be amendable to dopamine replenishment therapy [15] perhaps due to thalamo-cortical disinhibition resulting in an increase of BGthalamocortical signals to the primary and supplementary motor areas [19]. Conversely, other coordinative aspects of an action may be resistive to pharmacotherapy since these aspects may not be restored by a simple facilitation of the BG-thalamo-cortical pathways [15].…”
Section: Introductionmentioning
confidence: 99%
“…The impairment in voluntary movement in PD is characterized by a number of specific sensorimotor processing deficits, including a generalized slowness of movement; 3 a difficulty in carrying out sequential movements; 4 a reliance on sensory input, particularly visual input, to guide and correct movement; 5,6 and difficulties in timing, synchronizing, and coordinating movements. [7][8][9] Since Parkinson's disease is a degenerative disease, an effective tool is needed to track changes in its severity and the effectiveness of remedial treatments. Clinical evaluations can be costly and difficult to execute consistently over the long duration of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive procedures, such as DBS of the subthalamic nucleus show improvements of motor performance in many patients (for meta-analysis, see Boucai et al [ 123 ]). A recent study by Schettino et al [ 124 ] showed that STN DBS resulted in a more normal pattern of hand preshaping when reaching to grasp an object, a pattern not seen with dopaminergic therapy in a previous study [ 8 ]. Specifi cally, when reaching towards an object that was convex on one side (Fig.…”
Section: Pathophysiology Of Motor Dysfunction In Pdmentioning
confidence: 86%
“…Thus, when visual feedback of the object and/or the hand is removed during the reach, PD patients take signifi cantly longer to transport the hand to the object, especially at close range to the target, while producing a greater than normal grip aperture [ 64 ]. Removal of visual feedback of the hand during the reach also exacerbates inappropriate hand preshaping and results in signifi cantly more failed grasps [ 8 ].…”
Section: Grasping and Functional Hand Controlmentioning
confidence: 99%